How is Early Barrett’s Cancer Currently Diagnosed and Treated in Western Europe? Results of a Survey at 52 University Hospitals in Eight Western European Countries - Heuberger, D.; Manner, H.; Ell, C.; Pech, O. (Zeitschrift für Gastroenterologie, 2012)
Background and study aims: Endoscopic treatment is increasingly being accepted for early Barrett’s cancer (EBC), as it is associated with few complications, excellent long-term results, and almost no mortality. This study investigated current standards and treatment strategies for EBC in eight countries in Western Europe.Methods: A standardized questionnaire with questions on the endoscopic diagnosis, staging, and treatment of EBC was developed and sent to 107 university gastroenterology departments. The data were analyzed anonymously.Results: The response rate was 49 % (52/107). For work-up of early Barrett’s neoplasia, 67 % of hospitals use high-resolution endoscopes, with routine four-quadrant and targeted biopsies of visible lesions in 94 % of the cases. Narrow-band imaging and chromoendoscopy are used in 67 % of the cases, and other advanced imaging and staining techniques in 65 %. Before treatment, 63 % of the respondents recommended conventional endosonography, 6 % miniprobe endosonography, and 19 % both. Endoscopic resection is carried out at 98 % of the hospitals. Argon plasma coagulation is used for ablation in 52 % of the cases and radiofrequency ablation in 27 %. An 80-year-old patient with localized mucosal EBC would be treated endoscopically in all of the hospitals. Endoscopic therapy was recommended for 50-year-old patients with mucosal EBC by 87 % of the hospitals; esophageal resection was recommended for multifocal EBC by 15 % in 80-year-old patients, by 63 % in 50-year-old patients and by 44 % in patients with incipient submucosal infiltration.Conclusions: About two-thirds of the university hospitals use high-resolution endoscopy and advanced imaging. Endoscopic therapy is the accepted standard for treating localized mucosal Barrett’s cancer in Western Europe; esophageal resection is recommended by the majority (63 %) for a young patient with multifocal EBC.
Keywords: esophagus; Barrett’s esophagus; esophageal cancer